A Steady State ANN Model for the Operational Characteristics of a Variable Speed (VS) Direct Expansion (DX) Air Conditioning (A/C) System - Li Zhao; Deng Shiming (Zhileng xuebao)
In this study, an ANN model for an experimental VS DX A/C system was developed to predict its outputs with an assumption that the indoor air states will not influence the relative value of system outputs. Steady state experiments under a fixed indoor air state were carried out in this study to obtain the operational characteristics of the system for training and testing the ANN model and the ANN model developed was validated through steady state experiments under the non-training indoor air state. The experimental results showed that the max errors of prediction in training, testing and validating were below 5% and the average errors were below 3%, suggesting that the ANN model developed was capable of predicting the system outputs with satisfactory accuracy at both training and non-training indoor air states.